(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
This paper presents the representation of Lie groups and Lie algebras with precisely two areas of its applications. We starting on the level of explaining the basic concept of Lie groups, which we then review some connections between Lie groups and Lie algebras and then to their representation and we finally considered its applications in differential equations and harmonic oscillators and currents.